Essensi Media dan Teaching Media: Wejangan Untuk Pengguna - Sribagus Sribagus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2019)
Abstract : Some teachers think that the use of teaching media in class is not so important. Probably they think so because they have adequate experience in teaching so that they can do their job with no barriers at all. Their ego drives them to a sort of contradictive assumption that playing with teaching media is a pointless job. In turn they are confident enough to throw a wild proposal to drop the teaching media from the curriculum. They try to argue further that the so called media is already integrated in every subject matter. Others, however, think that keeping as well separating this subject doesn’t cause any harm and laziness. On the other hand, it brings sharper insight to any users. To get rid of wild debate, vivid solution is then worth pointing in this article.Keywords : Teaching media, pengajaran, pembelajaran, seribu satu